Getting traditionally rooted Indian leadership to embrace digital leadership: Challenges and way forward with reference to LMX - Shalaka Sharad Shah; Sairaj Milind Patki (Leadership, Education, Personality. An Interdisciplinary Journal, 2020)
Leadership has been a topic of great interest for researchers, business people, educators, and government officials alike over the years. Leadership as a theoretical construct has undergone a great deal of changes as a result of changes such as modernization, globalization and most recently digitalization. Taking into account the various changes that the internet and cloud computing has introduced in the organizational systems and processes across the globe, it is prudent to understand the relationship between leadership and digitalization to foresee how leaders should prepare themselves to cater to the challenges of the future. Leadership is indeed an ever-evolving concept, and so is technology; of which digitalization is an outcome. Most inquiries about such a relation are being well executed by the western cultures. Exploring the relationship between leadership and digitalization in the eastern cultures, especially India becomes more significant; as the technology is booming and drastically changing how daily activities are carried out as an influence of digitalization. With over 40% of the Indian population subscribed to the internet, and through the efforts made by the public and private sectors, India is on the way to being a technologically advanced country. India is also the largest base of digital consumers. Leaders struggle to lead in such challenging situations; which are becoming more volatile. It is imperative to examine what capacities, abilities and competencies leaders already have and what they need to further improve upon, in order to lead effectively in the digital world. To examine the overall context of Indian traditional leadership, leader-member exchange is seen to be a relevant theory. At last, challenges and gaps are discussed and the notion of "creative personality" is recommended for Indian leaders to cater to the digital changes.
Keywords: 330; Digital leadership; India; LMX; Digitalization; Competencies; Creative personality